Synthesis of 3,3-dimethyl-6-oxopyrano[3,4-c]pyridines and their antiplatelet and vasodilatory activity - Sirakanyan, Samvel N; Hrubša, Marcel; Spinelli, Domenico; Dias, Patrícia; Kartsev, Victor; Carazo, Alejandro; Hovakimyan, Anush A; Pourová, Jana; Hakobyan, Elmira K; Karlíčková, Jana; Parvin, Shamima; Fadraersada, Jaka; et al. (The Journal of pharmacy and pharmacology, 2022)
OBJECTIVES: Both pyridine and pyrano derivatives have been previously shown to possess biologically relevant activity. In this study, we report the incorporation of these two scaffolds into one molecule. METHODS: The designed 3,3-dimethyl-6-oxopyrano[3,4-c]pyridines were synthesized by the acylation of enamine under Stork conditions followed by condensation of formed β-diketones with 2-cyanoacetamide. The structures of these compounds were confirmed by using a wide spectrum of physico-chemical methods. Their antiplatelet, anticoagulant and vasodilatory activity together with toxicity were evaluated. KEY FINDINGS: A series of 6-oxopyrano[3,4-c]pyridines 3a-j was obtained. Four of these compounds were reported for the first time. None of the tested compounds demonstrated anticoagulant effect but 8-methyl derivative (3a) was a potent antiplatelet compound with IC50 numerically twice as low as the clinically used acetylsalicylic acid. A series of further mechanistic tests showed that 3a interferes with calcium signaling. The compound is also not toxic and in addition possesses vasodilatory activity as well. CONCLUSIONS: Compound 3a is a promising inhibitor of platelet aggregation, whose mechanism of action should be studied in detail.
Keywords: pyridiny; inhibitory agregace trombocytů; anticoagulant; β-diketones; vztahy mezi strukturou a aktivitou; Pyridines; pyranopyridine; vasodilatory; agregace trombocytů; antiplatelet activity; cytotoxicity; Anticoagulants; antikoagulancia; Platelet Aggregation; Structure-Activity Relationship; Platelet Aggregation Inhibitors